Tuning lattice spacing in titanate nanowire arrays for enhanced sodium storage and long-term stability. (March 2018) - Que, Lanfang; Yu, Fuda; Zheng, Lili; Wang, Zhen-Bo; Gu, Daming
Abstract: Fabricating high-performance anode materials is of great significance for the realization of advanced Na-ion batteries (SIBs). Poor rate capability and insufficient cycle stability are two main scientific issues urgently needing to be solved for sodium titanate (Nax Tiy Oz ) anodes. In this paper, protonated titanate nanowire arrays are designed rationally as novel additive-free anodes for SIBs. Results reveal that the protonated strategy can controllablly regulate the lattice interlayer spacing of the titanate, which can not only effectively facilitate the Na-ion migration but also suppress the side reaction and inhibit the irreversible trapping of Na-ions in the crystal framework, leading to fast Na-ion diffusion kinetics. Moreover, the protonated titanate material experiences smaller changes in lattice parameters and unit-cell volume during long-term cycling than those of non-protonated material, resulting in less mechanical stresses and capacity loss in an anode. As expected, the protonated titanate material exhibits superior rate performance and ultralong lifespan when utilized as free-standing anode for SIB, remaining 85% capacity retention after 8000 cycles at 5.0 A g −1 ( 23 C). When assembled as full cell with Na3 V2 (PO4 )3 cathode, high energy density (262.3 Wh kg −1 ) and power density (1748.9 W kg −1 ), excellent rate capability and superior cycle stability (260 cycles, 86%) can be achieved. Graphical abstract: The lattice spacing of sodium titanate nanowire arrays is tuned by a protonation strategy, which can (1) enhance the Na-ion diffusion by offering more effective Na-ion diffusion channels; (2) stabilize the electrode structure by reducing the changes in lattice parameters and unit-cell volume during long-term cycling; (3) inhibit the irreversible trapping of Na-ions and side reaction, and all these merits lead to superior rate capability and cycle stability as anode for SIBs.fx1 Highlights: HTO nanowire arrays with tuned lattice interlayer spacing can effectively offer quick and easy electron and Na-ion flow. HTO anode inhibit the irreversible trapping of Na-ions and side reaction. HTO remans 85% after 8000 cycles at 5.0 A g- 1 ( 23C) as SIB anode. High energy/power densities and superior cycle stability can be achieved when assembled as full cell with Na3 V2 (PO4)3 .